1996
DOI: 10.1046/j.1365-3083.1996.d01-78.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of MPT83: a Seroreactive Antigen of Mycobacterium tuberculosis with Homology to MPT70

Abstract: The Mycobacterium bovis antigens MPB70 and MPB83 are homologous cross-reactive proteins. It has been reported previously that MPB83 is glycosylated and exists in two forms with apparent molecular masses of 23kDa and 25kDa, whereas the apparent molecular mass of MPB70 is 22kDa. Using a monoclonal antibody, SB10, which recognizes an epitope common to both MPB70 and MPB83, we compared the expression of these proteins in M. bovis BCG, virulent M. bovis and virulent Mycobacterium tuberculosis by Western blotting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
102
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 46 publications
6
102
0
1
Order By: Relevance
“…They suggested that the increases in molecular weight, relative to the 22,000 MPB70, were attributable to glycosylation with mannose, as treatment of these antigens with ␣-mannosidase resulted in a reduction in their relative molecular weight. Subsequently, we demonstrated the presence of a gene, mpb83, which encodes a protein with 61% identity at the amino acid level to MPB70 (18). In the same study, the protein encoded for by this gene, MPB83, was shown to bind a monoclonal antibody specific for the 25/23-kDa M. bovis antigen.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…They suggested that the increases in molecular weight, relative to the 22,000 MPB70, were attributable to glycosylation with mannose, as treatment of these antigens with ␣-mannosidase resulted in a reduction in their relative molecular weight. Subsequently, we demonstrated the presence of a gene, mpb83, which encodes a protein with 61% identity at the amino acid level to MPB70 (18). In the same study, the protein encoded for by this gene, MPB83, was shown to bind a monoclonal antibody specific for the 25/23-kDa M. bovis antigen.…”
mentioning
confidence: 76%
“…The data shows that the 23-kDa form of MPB83 is generated by proteolytic cleavage immediately before Thr 48 from the mature acylated 25-kDa form (18). This raises the possibility that glycosylation may function either as a signal for cleavage or as a means of preventing amino-terminal degradation of the protein following cleavage from its acylated anchor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MPB70 and MPB83 are both expressed constitutively in M. bovis yet are expressed only at very low levels in BCG strains that have lost the RD2 regions, such as BCG Pasteur, which was used in the present study (20,33). MPB70 is a secreted protein (21), whereas MPB83 is a cell wall-associated glycolipoprotein that is also found in culture filtrates (11). The proteins are highly homologous at the amino acid level (11) and are major constituents of PPD-B (K. Lyashchenko, A. O. Whelan, and H. M. Vordermeier, unpublished data), which would explain why the immune responses to these antigens were boosted by tuberculin skin testing.…”
Section: Fig 1 Boost Of Mpb70 and Mpb83mentioning
confidence: 99%